NIAT WHISTLEBLOWING: STUDI EKSPERIMEN PADA MAHASISWA AKUNTANSI DI INDONESIA - Miftahul Jannah; Zusma Widawaty A. Wahab (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
Indonesia is a country that has initiated whistleblowing in 2018, but it can only be implemented in 2021, after previously in early 2021 a Memorandum of Understanding (MoU) with the corruption eradication commission was carried out. The whistleblowing system is an effective way to tackle fraud through empowering whistleblowers. This research was conducted with the aim of knowing the effect of ethical decision making, moral intensity, religiosity, and materiality level on the intention to undertake whistleblowing. This research is experimental based, while the respondents consist of accounting students at all universities in Indonesia, both State Universities (PTN) and Private Universities (PTS). This research was conducted by giving a case regarding whistleblowing to students, then the student answered several statements related to the given case. Data was collected by distributing questionnaires in the form of Google Forms, which were distributed online through social media. Data analysis was performed using SEM-PLS (Structural Equation Modeling – Partial Least Square). The results showed that the influence of ethical decision making, moral intensity, religiosity had a positive and significant effect on whistleblowing intentions.